FATWA HUKUM MEROKOK DALAM PERSPEKTIF MUI DAN MUHAMMADIYAH - Ali Trigiyatno (Jurnal Penelitian, 2011)
Muhammadiyyah and MUI (Indonesian Ulama Council) – with a slight intention – have finally revealed their advice about smoking. These two advices were deserved to be called into questions in: what the (Islamic) legal proposition (dalil/hujjah) and the istinbath method (istinbath al-hukm). They both, easily change the advice about smoking from neutral deeds (mubah) into avoidance (makruh), and then into forbidden (haram). These evolutional alterations drew my attention to examine their way of taking istinbat, that conclude smoking as avoidance or forbidden. In the way of research, I was using qualitative- normative approach for getting answer to the causes of their conclusion. The result showed us, they both using bayani approach and istishlahi one, so the qiyasi methode. The difference of them, was situated at how many syari’ah maxims that they cited on their fatwa: MUI cited many more than Muhammadiyah.